Rationing Rules and Outcomes : The Experience of Singapore's Vehicle Quota System - Tan, Ling. (Washington, D.C. : International Monetary Fund, 2001)
Since 1990, Singapore has sought to control motor vehicle ownership by means of an auction quota system, whereby prospective vehicle buyers need to obtain a quota license before they can make their purchase. This paper assesses the success of the vehicle quota system in meeting its objectives of stability in motor vehicle growth, flexibility in the motor vehicle mix, and equity among motor vehicle buyers. Two important implementation issues-quota subcategorization and license transferability-are highlighted, and policy lessons are drawn for the design of auction quotas in general.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet